The Absence of the Financial Investigation in the Slovak Republic and its Consequences - Kurilovská, Lucia; Kordík, Marek (Public Governance, Administration and Finances Law Review, 2016)
According to current status financial investigation is not established by the Criminal Procedural Code or other legal source in a formal way in Slovakia. The study analyses this situation de lege lata and de lege ferenda.